Analisis Model Pembelajaran Kooperatif Tipe Two Stay Two Stray (TSTS) Sebagai Upaya Meningkatkan Motivasi Belajar Siswa - Dewi Masyithoh Al Falah; Brillian Rosy (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
This article aimed to analyze how the two stay two stray type of cooperative learning model can increase student motivation in general administration subjects. Basic competence regarding understanding administration aimed at students to explain, classify and differentiate types of administration. The two stay two stray cooperative learning model is the right model to increase student motivation, because the learning model can build teams, social skills, build knowledge, learning procedures, process information, think skills, and present information. In the implementation of this learning model student-centered to help students more actively think, be responsible, and increase student learning motivation. This type of research is conceptual which proves that the two stay two stray cooperative learning model as an effort to increase student motivation.